Deep preferential trade agreements and export efficiency in Ghana: Do institutions matter? - Camara Kwasi Obeng; Michael Tutu Boadu; Ewura-Adwoa Ewusie (Research in Globalization, 2023)
Preferential trade agreements with environmental provisions (Deep PTAs) have introduced a new layer of costs to bilateral trade. For a country seeking to grow its exports to generate sufficient foreign exchange for economic transformation, it is essential to investigate the effects of the expanded preferential trade area on its export efficiency. Therefore, this paper, employs the stochastic frontier gravity model to investigate Ghana's bilateral export efficiency using a panel of 44 of her export destination countries for the period 2007 to 2019. The paper finds that Ghana's bilateral export trade is inefficient, implying huge potential exists. It further reveals that PTAs with environmental provisions reduce Ghana's export efficiency. The reduction in export efficiency lessens with improvement in institutional quality. The paper recommends that the regulatory roles of Ghana Standards Authority and the Environmental Protection Agency should be strengthened to ensure that exporters meet target market regulations to continue to benefit from the bilateral PTAs. Given the negative effect of the exchange rate on export efficiency, the Bank of Ghana and the Ministry of Finance should urgently enhance macroeconomic stability to provide a stable platform which should promote the country's export value and volume.
Keywords: 330; Deep PTAs; Export; Export efficiency; Ghana